Using crop diversity to adapt to climate change: highlighting the importance of the Plant Treaty's policy support - Halewood, Michael; Mathur, P.N.; Fadda, Carlo; Otieno, G. (2013)
This brief highlights efforts in East Africa and in Asia, Pacific and Oceania (APO), supported by two internationally funded projects, to develop user-friendly tools and methods to identify germplasm of populations/varieties/species that are adapted to the changing climates of areas where farmers’ cropping systems are already under stress. The brief highlights the importance of the Plant Treaty’s policy support for these activities.